EFEKTIVITAS PENGGUNAAN ALAT INSTAN DALAM PENERJEMAHAN TEKS BAHASA ARAB - Mas’udah Mas’udah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to analyze the effectiveness of instant translation tools based on artificial intelligence in translating Arabic texts into Indonesian. The tools examined include Google Translate, Deep Translator, and ChatGPT, which represent widely used AI-based translation technologies in educational and academic settings. This research employs a descriptive qualitative method by collecting primary data from the translation outputs of the three tools, as well as secondary data from literature related to translation studies and artificial intelligence. The findings indicate that instant translation tools provide convenience, speed, and efficiency in translating words, phrases, and simple sentences. However, notable limitations remain in terms of grammar, morphology, semantics, idiomatic expressions, and cultural context, especially when dealing with complex or religious texts such as Qur’anic verses. A comparison with human-produced translations shows that human translators are still superior in capturing contextual meaning and cultural nuances. Therefore, while instant translation tools are valuable as supporting media for learning and initial comprehension, human intervention is still required to produce translations that are accurate, meaningful, and contextually appropriate.